Linezolid-resistant Enterococcus gallinarum isolate of swine origin carrying cfr, optrA and poxtA genes. (23rd November 2021) - Coccitto, Sonia Nina; Cinthi, Marzia; Fioriti, Simona; Morroni, Gianluca; Simoni, Serena; Vignaroli, Carla; Garofalo, Cristiana; Mingoia, Marina; Brenciani, Andrea; Giovanetti, Eleonora
Abstract: Objectives: To characterize a linezolid-resistant Enterococcus gallinarum isolate of porcine origin co-carrying cfr, optrA and poxtA genes. Methods: The genome was sequenced using the Illumina and Nanopore platforms. The presence of circular intermediates was examined by inverse PCR. Transferability of oxazolidinone resistance genes was investigated by transformation and conjugation. Results: Two plasmids, the cfr - and optrA -carrying pEgFS4-1 (35 kb) and the poxtA- harbouring pEgFS4-2 (38 kb), were identified. pEgFS4-1 disclosed a distinctive mosaic structure with two cargo regions bounded by identical IS 1216 elements interpolated into a backbone related to that of Enterococcus faecium vanA -containing pVEF2. The first cargo region included the cfr and optrA contexts, whereas the second one carried a Tn 554 remnant and the lnu (A) gene. Both regions were able to excise in circular form as a unique translocable unit. pEgFS4-2 plasmid was 99% identical to a not fully described E. faecium pSBC1 plasmid. The poxtA environment, flanked by IS 1216, was proved to be unstable. pEgFS4-2 also exhibited another cargo region containing the tet (M)– tet (L) genes arranged in tandem and its circular form was detected. Transformation and conjugation experiments failed to demonstrate the transferability of both plasmids to enterococcal recipients. Both plasmids persisted in the absence of selective pressure. Conclusions: To the best of our knowledge, this is the first description of a linezolid-resistant E. gallinarum isolate of swine origin carrying cfr, optrA and poxtA genes. The co-presence of three linezolid resistance determinants in an intrinsically vancomycin-resistant enterococcal species is cause of concern.